Socio-economic development of enterprises in a permanent crisis - Naida, Andriy; Sitkovska, Alla; Shevchenko, Alisa; Palii, Svitlana; Shved, Tetyana (My University, 2022)
In the article reviews the impact of the crisis on the socio-economic development (SED) of the enterprise and directions of work for the implementation of eﬀective crisis management. To develop a systematic approach to the formation of SED strategy. A systematic approach to the formation of the SED strategy of the enterprise as a tool to ensure eﬀective crisis management has been developed. The main tasks of this strategy are deﬁned. The directions of work of managers for realization of eﬀective anti-crisis management were formulated. У статті розглянуто вплив кризи на соціально-економічний розвиток (СЕР) підприємства та напрями роботи щодо впровадження ефективного антикризового менеджменту. Розробити системний підхід до формування стратегії СЕД. Розроблено системний підхід до формування стратегії СЕД підприємства як інструменту забезпечення ефективного антикризового управління. Визначено основні завдання цієї стратегії. Сформульовано напрямки роботи менеджерів для реалізації ефективного антикризового управління.
Keywords: permanent crisis; socio-economic development; development strategy; anticrisis management; перманентна криза; соціально-економічний розвиток; стратегія розвитку; антикризове управління; кафедра економічної теорії